Resistance induction in chrysanthemum due to silicon application in the management of whitefly Bemisia tabaci Biotype B (Hemiptera: Aleyrodidae) - Bruno Almeida Melo (Revista de Ciências Agroambientais, 2015)
Whitefly Bemisia tabaci biotype B (Hemiptera: Aleyrodidae) is a key pest in many cultures worldwide, among them chrysanthemum. The aim of this study was to evaluate whether silicon application in chrysanthemum plants can induce resistance to whitefly. The experiments were conducted in chrysanthemum cv. Rage in a greenhouse at EPAMIG in São João Del Rei, MG. The treatments were: 1) silicon applied as soil drench (dosage of 2t SiO2/ha) on the 4th day after planting, 2) two silicon applied as foliar spray on the 4th and 12th days after planting, 3) control, with 10 replications each. The plants were infested with 100 whitefly adults/pot, released 16 days after planting. The number and viability of whitefly eggs and number of nymphs and adults were evaluated. The production of fresh and dry matter of shoots and the silicon content in plants were also evaluated. Silicon did not affect the whitefly oviposition preference; however, it affected the development of nymphs in free-choice test. Foliar silicon applications reduced the viability of whitefly eggs. There was no difference of fresh and dry weight and silicon content in plants with the application of silicon. Therefore, foliar silicon application on chrysanthemum can reduce the viability of eggs and delay the development of nymphs and thus contribute to the integrated whitefly management in commercial crops.